Employee Involvement Mediates the Relationship between Strategy Formulation and Implementation: the case of Rural and Community Banks in Ghana - Ackah, Abena (European Journal of Business and Strategic Management, 2023)
Purpose: This study investigates the mediating role of employees in strategy formulation and implementation in rural banks in Ghana. Methodology: The researcher surveyed 360 respondents from rural and community banks in Ghana. Two hundred (270) respondents responded out of the 360 expected responses, representing a 75% response rate. The researcher used Amos graphics to examine employee involvement in the mediation role in the relationship between strategy formulation and implementation. Findings: The relationship between strategy formulation and implementation was accepted (Î² = .0505, p = 0.000 < 0.05), the effectiveness of strategy formulation predicted the effectiveness of strategy implementation, and the employee mediation role between strategy formulation and implementation was accepted (Î² 0.140, p = 0.046 < 0.05). Employee mediates strategy formulation and implementation and predicts the effectiveness of strategy implementation. Unique Contribution to Theory, Practice and Policy: The study investigated the relationship between strategy formulation and implementation in the rural and community banks in Ghana and the role of employees in the relationship between strategy formulation and implementation, a theoretical contribution made to the field in the strategic management process. There is limited current literature that has examined the mediating role of employees between strategy formulation and implementation in the rural and community banks in Ghana or used the variables in this study to make predictions and conclusions on employee role in the relationship between strategy formulation and implementation. The study recommends that strategy formulation should not be an exclusivity right for top managers and must be an all-inclusive process where all stakeholders within the RCBs are involved in the strategy formulation process, selecting the stakeholders from middle management, lower management, and employees. The selection must be limited to functional heads, unit heads, and employees with strategic roles and responsibilities to provoke positive strategic outcomes, leadership to encourage creativity, knowledge sharing among staff for new thinking perspectives and methodologies in the banks' product and service offerings.